O mercado sobe a favela: um estudo sobre o Santa Marta pós-UPP - Ost, Sabrina Marinho (2012)
This case study aimed to identify how the implementation of the Unidade de Polícia Pacificadora ('Pacifying Police Unit,' or UPP) in Santa Marta favela, Rio de Janeiro, has changed the interaction of the market with this community and how it affected social relations in the slum, according to the perception of the residents. The objective of this research was to understand how the internal market, be it formal or informal, has responded to the new situation and how actors from the external market, as Firjan, Light, among others, have been working on site. Moreover, we aimed to examine how this new market dynamics, made possible by greater state presence in Santa Marta, influenced local sociability. Furthermore, we carried out a field research where observations and semi-open interviews were conducted with representatives of companies that operate in the favela, as well as local entrepreneurs, residents and local leaders. We found that the expansion of the internal market and external market activity in the favela, allows some benefits to reach those who live there. However, this situation has generated new insecurities to residents who feel that increased tourism and festivities to the general public have been restricting leisure facilities. We also found that they fear not being able to afford the rising costs of living there and the consequent impoverishment, as well as they fear that they will suffer a process of banishment caused by market pressure. Thus, some will be able to take advantage and even promote themselves through the opportunities that have arisen with the expansion of the market, while others probably won’t have the capability and will suffer a new exclusion.